Respuesta :
Let's solve this problem step-by-step.
STEP-BY-STEP SOLUTION:
Let's establish equations for each of the individuals as displayed below:
Let Tom = t
Let Geraldine = g
Let Steven = s
Tom -
t = t
Geraldine -
g = t - 4
Steven -
s = 2g
s = 2 ( t - 4 )
s = 2t - 8
ANSWER:
As there is no further information given for this problem, our answer is:
Geraldine = t - 4 years old
Steven = 2t - 8 years old
Hope this helped! <3
STEP-BY-STEP SOLUTION:
Let's establish equations for each of the individuals as displayed below:
Let Tom = t
Let Geraldine = g
Let Steven = s
Tom -
t = t
Geraldine -
g = t - 4
Steven -
s = 2g
s = 2 ( t - 4 )
s = 2t - 8
ANSWER:
As there is no further information given for this problem, our answer is:
Geraldine = t - 4 years old
Steven = 2t - 8 years old
Hope this helped! <3
I. Geraldine's age is equal to [tex]t-4\;years\;old[/tex]
II. Steven's age is equal to [tex]2t-8\;years\;old[/tex]
- Let the age of Geraldine be G.
- Let the age of Tom be T.
- Let the age of Steven be S.
Given the following:
- Tom's age = t years
Translating the word problem into an algebraic expression, we have;
For Geraldine:
[tex]G = T-4[/tex] ...equation 1.
For Steven:
[tex]S = 2G[/tex] ...equation 2.
To find the age of Geraldine:
Substituting Tom's age into eqn. 1, we have:
[tex]G = t-4 \; years[/tex]
To find the age of Steven:
[tex]S = 2(t-4)\\\\S=2t-8\; years[/tex]
Read more: https://brainly.com/question/6463206